Exploring The Dynamics of Inflation, Interest Rates, and Us Dollar Exchange Rates: A Comprehensive Quantitative Analysis From 2013 To 2023 - Yee, Edd Mund; Chan, Tze-Haw (The Asian Journal of Technology Management (AJTM), 2024)
Abstract. This study examines the relationships between inflation, interest rates, and US dollar exchange rates from 2013 to 2023. The main objective is to evaluate the value of the US dollar (USD) and understand how key economic indicators interact. Using advanced quantitative analysis, we identify patterns that define these variables. A macro model incorporating the natural logarithms of the USD Index (USDX), Federal Funds Rate (FFR), and Consumer Price Index (CPI) addresses time-related and growth factors. By tracking inflation, interest rates, and dollar fluctuations, we gain insights into the factors influencing the US economy. The findings highlight the slow adjustment of inflation towards long-term stability and reveal significant causal relationships among the variables. As global financial conditions evolve, this study offers relevant insights for policymakers, economists, and market participants on navigating the dynamics of inflation, interest rates, and exchange rates in today's economic landscape. Keywords: Inflation; exchange rate; the United States; fed; fed funds rate